Role of CTLA4 immunohistochemistry in the diagnosis of colon cancers - Vishnu Narayanan; V Pavithra; Divya Dhanapal; Sandhya Sundaram; C D Narayanan (Wolters Kluwer Medknow Publications, 2022)
Background: There are a wide range of diagnostic markers for colorectal cancers like detection of mutated KRAS, TP53, and APC genes. However, genetic and immunological factors have also been attributed to the cancer prognosis. The present study was carried out to evaluate the expression of CTLA-4 in colorectal cancers. Methods: This cross-sectional study was carried out among 30 resected specimens of colorectal cancer. Paraffin blocks were made on samples from tumor areas along with adjacent normal areas. Immunohistochemistry for CTLA-4 was done on the sections along with controls. Gross findings were recorded from the blocks. Blocks with section containing normal epithelium and tumor were chosen for immunohistochemistry. Results: Overexpression of CTLA-4 was observed in 43.3% of the tumors. There was a significantly high tumor infiltration among those specimens showing overexpression of CTLA-4. The observed difference was statistically significant (P < 0.05). On comparing the grade of the tumor with intensity of CTLA4 uptake, it was observed that majority of the well-differentiated tumors (66.7%) had an intensity of 1+ whereas majority of the poorly differentiated tumors had an intensity of 3+ (66.7%). Conclusion: The present study has demonstrated overexpression of CTLA-4 in colorectal cancer specimens, and also highlighted the potential scope for anti-CTLA-4 agents like Ipilimumab in cancer therapy. The need for further evaluation to examine five-year survival with such immunotherapies is essential to document candid therapeutic recommendations for colorectal cancers.